That's impossible for me: the genre and pragmatic strategy chosen by Spaniards and Brazilians when refusing in digital and academic interactions - González, Sara Berrio; Leralta, Susana Martín; Rocha, Nildicéia Aparecida [UNESP] (Servicio de Publicaciones de la Universidad de Cadiz, 2021)
This article empirically analyzes the genre and pragmatic strategy chosen by 30 Spanish and 30 Brazilian university students. In order to achieve this goal, both groups conducted a DCT composed of eight academic situations with different relative power, social distance and power rankings. In each situation they had to decide whether to send an e-mail or a private message on Facebook. The data gathered from the corpus shows that the Brazilians have a slight preference for private messages on Facebook whereas the Spaniards demonstrated an orientation toward e-mails. However, both groups had a predilection for direct strategies, especially when refusing in low power rank or high social distance situations. All in all, there are pragmatic differences hidden behind the false image of transparency that related languages share. It is necessary to unveil them in order to avoid pragmatic failures and achieve successful cross-cultural interactions.
Me es imposible: elección del género discursivo y estrategias pragmáticas del rechazo en la comunicación académica digital de españoles y brasileños
« C'est impossible pour moi » : le choix du genre discursif et des stratégies pragmatiques du refus dans la communication académique et numérique des espagnols et des brésiliens
Keywords: Brazilians; Cross-cultural pragmatics; digital genres; refusals; Spaniards